Silver and Gold Nanoparticles: a Toxicological Aspect - Dang, Minh Hieu (Old Journal, 2017)
Silver and gold nanoparticles have been found in vast number of applications, especially in medicine. With increasing and intensively uses of these nanoparticles, there is a growing concern, recently, on their environmental impacts when they are released into environments. In this study, the size and shape- dependent cytotoxicity of silver and gold nanoparticles have been examined. Silver nanoparticles inhibited the growth of the mold Aspergillus niger, and the one-dimension (Np1) and two-dimension (Np2) nanoparticles indicated more effective than the round ones (Np0). On the other hand, gold nanoparticles of the three types: nanostars (AuNS), polyethylene glycol coated nanostars (PEG-NS) and TAT peptide tagged nanostars (TAT-NS), placed impact on the BT549 human breast cancer cells with reduction in the cell viability. The PEG-NS showed more remarkable impact on the cells in compare to the others.